Features of biochemical parameters and non-specific resistance factors of vaginal contents in women with urogenital trichomoniasis and cervical intraepithelial neoplasia against the background of papillomavirus infection - O.A. Dyndar; V.O. Beniuk; T.V. Kovaliuk; T.R. Nykoniuk; O.S. Neymark (Publishing House TRILIST, 2022)
Research objective: to improve the effectiveness of diagnosis and prognosis of complications in women of reproductive age with atypical squamous cells of undetermined significance/cervical intraepithelial neoplasia (ASCUS/CIN) of the cervix in Trichomonas and papillomavirus infection by studying the main biochemical and immunological parameters of vaginal contents. Materials and methods. 200 women of reproductive age with ASCUS/CIN of the cervix were examined against the background of papillomavirus infection associated with trichomoniasis, who were divided into three main groups according to the results of the PAP-test. Group I consisted of 50 patients with ASCUS, II - 118 women with LSiL, III - 32 patients with HSiL. The control group included 50 healthy non-pregnant women. The analysis of biochemical parameters of vaginal contents was carried out, which included determining the concentration of total protein, urea, studying mineral and lipid metabolism, glucose, enzyme activity, as well as factors of non-specific resistance - secretory immunoglobulin A and hydrogen peroxide. Results. There was a 2.6-fold increase in the amount of discharge from the genital tract and their pathological nature in patients with urogenital trichomoniasis and ASCUS/CIN against the background of papillomavirus infection, an increase in acidity by 1.2 times, the indicator of the amine test by 13 times, protein concentration by 2.3 times, compared with similar indicators in healthy women. Analysis of mineral metabolism in this contingent of patients revealed a decrease in the concentration of copper ions by 1.7 times, iron by 1.9 times, and calcium by 1.6 times. Evaluation of the enzyme activity revealed an increase in the level of alkaline phosphatase by 3.7 times, creatine phosphokinase by 10.6 times, AST by 6.5 times, ALT by 9.1 times, lactate dehydrogenase by 5.4 times, and α-amylase by 3.3 times compared to women in the control group. A decrease in the average value of sІgA content in patients with ASCUS/CIN on the background of HPV and Trichomonas invasion was found than in healthy women by 1.7, 1.9 and 2 times, respectively, in the I, II and III main groups, which can serve as a predictor of the development of post-trichomonas vaginal dysbiosis. Conclusions. Analysis of the results of studies of vaginal contents in women with ASCUS/CIN against the background of human papillomavirus and Trichomonas invasion revealed significant changes in biochemical parameters and factors of non-specific resistance, determining the corresponding pathological changes in the functional activity of the vaginal epithelium and the composition of the vaginal biotope.